OWNERSHIP OF LAND RIGHTS WITH THE STATUS OF PROPERTY RIGHTS BY FOREIGN NATIONALS AS BENEFICIARIES USING INDONESIAN CITIZENS - Nisa, Annisa Fitria (Universitas Pelita Harapan, 2023)
Normatively, the Government only grants land tenure rights to a foreigner in the form of right of use and lease rights. In practice, with various economic considerations and investment risks, foreigners willing to invest in Indonesia need to have land ownership with property status. Because property rights are hereditary rights, the most powerful and the most achievable, for a while. In this regard, the national land law policy does not allow foreign Nationals to have property rights on land in the territory of Indonesia. The prohibitions encourage foreigners with an interest in the Nominee Agreement, by using the persons of an Indonesian citizen as a Nominee to be registered as the owner of the land rights. Law Number 5 of the Basic Agrarian Law of 1960, especially Article 26 (2), prohibits such an agreements. The purpose of this research is to analyze the regulation and prevention of land nominees with a normative judicial research method. The primary legal materials used include land legislation and investment laws and regulations. The results of the study confirmed that the prohibition nominee agreements were regulated in Law Number 5 of 1960 of the Basic Agrarian Law but the sanctions against the nominee's practice were not yet clear and firm and the status of the land nominee had not been fully regulated. To ensure legal certainty, there is a need for arrangements regarding land nominees along with sanctions and the status of land rights that are used as nominee objects. Therefore, the government can cease and annul land rights if its not in accordance with as designations. The preventive measures of nominees can be done both through civil and criminal means by returning the land to the State.